Rehabilitation Management of Dystonia in an Adult with Mixed Cerebral Palsy - Navneet Kumar Chauhan; Anjana Babu; Shweta Jain (Indian Journal of Physical Medicine & Rehabilitation)
Dystonic cerebral palsy (CP) is a type of dyskinetic CP and causes involuntary muscle contraction and abnormal posture. The symptoms tend to increase when triggered by attempts to move and interfere with activities of daily living and quality of life. The rehabilitation regimen includes medications, spasmolytic injections and tailored physical and occupational therapies.